Evolución espacio-temporal de las unidades de ordenamiento ambiental (ZPB, ZPAES) y el refugio de vida silvestre de Los Pantanos de Villa, Perú (1987-2022) - Fabian Tolentino, Elveis Daniel (2024)
Coastal wetlands adjacent to urban areas, such as the Pantanos de Villa in the city of Lima, Peru, are subject to constant changes in land use due to anthropogenic interaction. This has led to the reduction of dense vegetation areas, giving way to built-up areas. Therefore, this article addresses the issue of the physical changes experienced in urban areas adjacent to the wetland, such as the environmental management units, in this case the Zone of Protection of Outcrop and Surface Runoff (ZPAES), and the Zone of Landscape Protection of Edge (ZPB), as well as the Pantanos de Villa Wildlife Refuge (RVSPV), as a result of rapid urban expansion. Therefore, the objective of this research is to analyze the spatial and temporal evolution of the Pantanos de Villa environment and urbanization within the Environmental Management Units ZPB, ZPAES, and RVSPV. To achieve this, the Google Earth Engine (GEE) platform was used, and satellite images from Landsat 5 TM and Sentinel 2 MSI sensors were processed. These images were worked on in the GEE interface and analyzed using spectral indices, NDVI and NDBI, through map algebra codes and pixel masking. For cartographic representation, a Geographic Information System (GIS) was used. The results show a 291.12% increase in built-up area and a 26% reduction in vegetated area over the last 35 years, for the Environmental Management Units ZPB and ZPAES, and the RVSPV. The identified reduction is directly related to unplanned expansion of urban areas and anthropogenic activities.